PENGARUH LAMA OZONISASI TERHADAP TOTAL PADATAN DAN VISKSOSITAS SUSU KAMBING PERANAKAN ETAWA (PE) - Hidayat, Taufik Nur; Santosa, R. Singgih Sugeng; Ifani, Merryafinola (ANGON: Journal of Animal Science and Technology, 2024)
Taufk Nur Hidayat. The research is entitled "The Effect of Ozonization Time on Total Solids and Viscosity of Etawa Crossbreed Goat Milk (PE)". This research aims to determine the effect of time ozonization of Etawa crossbreed goat milk on total solids and viscosity. This research was carried out experimentally using a Completely Randomized Design (CRD) which contained 5 treatments and 4 replications so that there were 20 experimental units. The materials used in this research were using Etawa crossbreed goat milk and equipment in the form of an ozone generator, with an ozone concentration used of 1000 mg/hour, an ice box as a place to store milk samples, a 1000 ml glass jar, 50 ml bakerglass, 300 ml jar bottle. ml, glass stirrer, label, tissue, lactoscan, and viscometer. The treatments used were ozonation periods of 0, 20, 40 and 60 seconds. The important variables observed in this research are total solids and viscosity. The results of the data obtained from the research that has been carried out are then analyzed using ANOVA. The results of the research on total solids and milk viscosity did not have a significant effect. The conclusion obtained from the research is that the length of ozonation has no effect on the total solids and viscosity of Etawa Peranakan goat milk (PE).​